Characteristics of composite nanofibers in the Sno2-Zno and Sno2-Tio2 systems as a photoanodes in dye-sensitized solar cells - Bakr, Z. H.; Jamil, Ismail; M., Abd Rahim; Yousefsadeh, M.; Ramakrishna, S.; Rajan, Jose (2018)
ZnO-SnO2 and TiO2-SnO2 composite nanofibers (CNFs) are synthesized by electrospinning a polymeric solution containing an equimolar concentration of the metals precursors and subsequent annealing. The composite formation is demonstrated by X-ray diffraction and energy dispersive X-ray measurements and morphology by scanning electron microscopy. Synergy in electronic and electrical properties are demonstrated by cyclic voltammetry, absorption spectroscopy, and electrochemical impedance spectroscopy. The TiO2-SnO2 and SnO2-ZnO CNFs offer valuable properties when utilized as a photoanode in dye-sensitized solar cells in terms of photoconversion efficiency (PCE ~8.00%) and (~5.60%), respectively, compared to their binary counterparts SnO2 (~3.90%), TiO2 (~5.1%) and ZnO (~1.38%).